Investigating the impact of headaches on the quality of life of patients with glioblastoma multiforme: a qualitative study. Issue 11 (16th November 2016) - Bennett, Samuel Robert; Cruickshank, Garth; Lindenmeyer, Antje; Morris, Simon Rhys
Abstract : Objectives: Headaches and facial pain have been identified as the most prevalent form of pain among patients with glioblastoma multiforme, the most common malignant primary brain tumour. Despite this, minimal research has been undertaken investigating the direct and indirect impact these headaches have on their quality of life. Therefore, in this study, we aimed at gaining a personal insight into the importance and impact that these headaches have on the quality of life of patients with glioblastoma multiforme. Design: Exploratory study using face-to-face semistructured interviews. Interviews were audio-recorded, transcribed verbatim and then qualitatively analysed using thematic analysis. Setting: Participants recruited from a tertiary referral hospital in Birmingham, UK. Participants: Purposive sampling of 14 registered outpatients recently diagnosed with glioblastoma multiforme. Results: 3 themes were identified: (1) an underlying attitude of determination and positivity; (2) impact of headache unpredictability on social interaction; (3) headaches found to act as a springboard onto thoughts regarding their disease and future. Conclusions: While the quality of life of patients with glioblastoma multiforme is clearly multifactorial, headaches do indeed play a part for some. However, it is not the direct pain of the headache as one might expect that impacts on the quality of life of these patients, but the indirect effect of headaches through limiting patients' social lives and by serving as a painful psychological reminder of having a life-threatening illness. In clinical practice, using headache diaries for these patients may help provide a more comprehensive assessment and further aid management plans. Alongside acting as an important reminder of the potential secondary implications of this disease, suggestions for future research include quantitatively investigating whether headaches can act as a prognostic indicator for quality of life within this patient demographic and determining whether these conclusions also hold true for a wider spectrum of patients with brain tumour.